2010
DOI: 10.1007/s10286-010-0099-x
|View full text |Cite
|
Sign up to set email alerts
|

Arterial baroreflex modulation influences postural sway

Abstract: Our study shows that postural sway is modulated by the ANS and is influenced by phasic stimulation of the arterial (carotid) baroreceptors. Our findings have potentially important clinical implications in the development of treatment strategies for pathological conditions in which alterations in posture and autonomic function coexist and could be mutually influenced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Although the precise neural pathway has not been established , recent work by Bernardi et al . demonstrated that carotid baroreflex modulation influences postural sway .…”
Section: Physical Counterpressure Manoeuvresmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the precise neural pathway has not been established , recent work by Bernardi et al . demonstrated that carotid baroreflex modulation influences postural sway .…”
Section: Physical Counterpressure Manoeuvresmentioning
confidence: 99%
“…Along these lines, Amberson [22] suggested the possibility of a connection between arterial baroreceptors and skeletal muscle tone, which could serve to increase muscle tensing during orthostasis. Although the precise neural pathway has not been established [2], recent work by Bernardi et al demonstrated that carotid baroreflex modulation influences postural sway [23].…”
Section: Muscle Tensingmentioning
confidence: 99%
“…Previous studies have shown that changes in cardiovascular autonomic control by arterial baroreceptor function manipulation may affect stance (7) and motor function by inhibiting spinal reflexes (36). On the other hand, activation of ergoreceptor associated fibers by the working muscle during gait results in profound changes in cardiovascular neural control, namely, an overall increase in cardiovascular sympathetic outflow (37).…”
Section: Cardiovascular Autonomic Changes After Mechanical Stimulatiomentioning
confidence: 99%
“…There is evidence of a functional interaction among neural somatosensory activation, and of motor and cardiovascular autonomic control both in health and disease. Indeed, the rhythmic perturbation of carotid baroreceptor afferents in healthy volunteers results in synchronous oscillations of postural sway (7). Also, the activation of plantar sensory afferents by electrical stimulation increases the arterial baroreflex sensitivity in patients with heart failure (17).…”
mentioning
confidence: 99%
“…Pressure fluctuations could be another cause of perturbation of quiet standing. Further support to the hypothesis that the sympathetic nervous system modulates postural sway is provided by a recent study (Bernardi, Bissa, De Barbieri, Bharadwaj, & Nicotra, 2011) that relies on phasic stimulation of the carotid baroceptors to demonstrate the influence of the autonomic nervous system on posture. Since the issue of the influence of the autonomic nervous system in balance could play an important role, further research is needed to fully understand the interrelations between autonomic activity and posture.…”
Section: Discussionmentioning
confidence: 90%